Defensive decision making: Operationalization and the relevance of psychological safety and job insecurity from a conservation of resources perspective - Stefanie Marx-Fleck; Nina M. Junker; Florian Artinger; Rolf van Dick (Journal of Occupational and Organizational Psychology, 2021)
Defensive decision making occurs when the decision-maker does not choose the option that is in the best interest of an organization or client but instead chooses a less effective but lower risk alternative that protects him or her in case something goes wrong. Such decisions are widespread across occupations and sectors and cause substantive damage to organizations. In a first step, we developed a scale to measure defensive decision making and test its validity. The scale covers two distinct but related dimensions: avoidance and approach. In a subsequent, two-wave study, we examined the antecedents of defensive decision making using conservation of resources theory as a theoretical lens. An environment characterized by higher psychological safety can reduce resource depletion and diminishes defensive decision making. In contrast, job insecurity can result in a threat to personal resources, which increases the likelihood that employees choose defensive decision​s. Practitioners points People engage in defensive decision making as a means to protect their own resources from exhaustion. Organizations can reduce the number of defensive decisions by enhancing situational resources such as psychological safety. The short and preliminarily validated scale we developed can be used to make defensive decisions visible in organizations.
Keywords: 650; conservation of resources theory; defensive decision making; organizational decision-making; psychological safety; scale development